Assessing the impact of heat stress on technical efficiency in rice production: evidence from Japanese farmers using a stochastic frontier approach - Xue, Rui; Mizuki, Asato; Kawashima, Shigekazu (Frontiers in Sustainable Food Systems, 2025)
BackgroundClimate change and associated heat stress threaten agricultural productivity, particularly rice production. Japan, characterized by its monsoon climate and heavy reliance on rice as a staple food, faces heightened risks from extreme temperatures. These conditions disrupt key physiological processes that are essential for rice yield and production efficiency.ObjectiveThis study investigates the impact of interannual temperature variability and heat stress on Japanese rice farmers’ technical efficiency (TE), emphasizing farm-level dynamics and climatic influences.MethodsBy using panel data from the Kome Seisanhi Chosa Tokei (2008–2016), this study employs a dynamic panel model estimated using System Generalized Method-of-Moments (SYS-GMM). The Heat Stress Index (HSI) is constructed based on cumulative heat exposure and consecutive high-temperature days, whereas the TE is estimated using stochastic frontier analysis (SFA).ResultsThe results reveal that heat stress significantly reduces TE, with marginal increases in HSI amplifying its negative effects. Rainfall variability has mixed impacts: abnormal rainfall during heading reduces efficiency, whereas additional rainfall during maturity enhances efficiency.ConclusionThese findings highlight the need for adaptive measures, such as heat-tolerant rice varieties and optimized resource management, to mitigate climate risks and enhance productivity.